2020
DOI: 10.1002/jgc4.1236
|View full text |Cite
|
Sign up to set email alerts
|

The gendered pay gap in genetic counseling

Abstract: A gendered pay gap in the genetic counseling profession has been identified in recent years, though reasons for its existence have not been explored in depth. The primary aim of this study was to determine what demographic characteristics and career experiences influence annual salary rates and which of those factors differ between male and female genetic counselors. The secondary aim of this study was to determine whether genetic counselors perceive a pay gap and to identify attitudes toward their salaries. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…A recent study of 355 NSGC members found male genetic counselors earn significantly more than female genetic counselors. A multiple regression model found males in non‐direct patient care roles earned $23, 736 more than females, and males in direct patient care roles earned $1552 more than females (Barnett et al., 2020). These results are consistent with findings from the 2021 NSGC professional status survey.…”
Section: Male Advantagementioning
confidence: 99%
“…A recent study of 355 NSGC members found male genetic counselors earn significantly more than female genetic counselors. A multiple regression model found males in non‐direct patient care roles earned $23, 736 more than females, and males in direct patient care roles earned $1552 more than females (Barnett et al., 2020). These results are consistent with findings from the 2021 NSGC professional status survey.…”
Section: Male Advantagementioning
confidence: 99%